Harmonising investment laws in the OHADA space - Mugangu, Marie Providence Ntagulwa (Department of Commercial Law, 2015)
The Organisation for the Harmonisation of Business Law in Africa (OHADA) was established for the purpose of restoring legal and judicial security in the region to attract more investment. The OHADA Treaty included certain areas of business law within its ambit but omitted investment law. There are several laws on investment in the region at the national, regional and sub-regional level that regulate the treatment of foreign investments such as CEMAC and UEMOA investment charters. Moreover OHADA states sign BITs to protect foreign investments. The relationship between the different sub regional laws on investment and OHADA is not yet clear but case law suggests that CEMAC and UEMOA courts recognise the supremacy of OHADA law and their lack of competence to hear matters regulated under OHADA. The standards of protection granted by OHADA states in BITs are very high thus taxing on them. This thesis suggests that OHADA states should either qualify these standards of protection or replace them with more specific provisions. The OHADA system of arbitration cannot effectively settle investment disputes arising out of a BIT leaving international arbitration systems such as ICSID as the best alternative to resolve investment disputes arising out of BITs.